2015
DOI: 10.1016/j.chom.2015.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Landscape of MicroRNA-Mediated Host-Virus Crosstalk during Productive Human Cytomegalovirus Infection

Abstract: Temporal profiles of miRNA activity during productive virus infection can provide fundamental insights into host-virus interactions. Most reported miRNA targetome analyses in the context of virus infection have been performed in latently infected cells and lack reliable models for quantifying the suppression efficacy at specific miRNA target sites. Here, we identified highly competent temporal miRNA targetomes during lytic HCMV infection by using AGO-CLIP-seq together with a bioinformatic method that quantifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(86 citation statements)
references
References 45 publications
1
77
0
8
Order By: Relevance
“…Many results suggest that hcmv-miR-US25-1, or hcmv-miR-US25-1-5p, is involved in diverse process; not only cell cycle control, but also virus replication inhibition as well as apoptosis regulation [5,6,32]. It has been reported that hcmv-miR-US25-1-3p has the ability to downregulate CDK6 gene associated with suppress cell cycle progression [19,33]. Here, we identi ed highly HCMV-miRNA expression pattern upon reactivation from latency in vivo, especially for hcmv-miR-US25-1-3p in autoimmune disease patient, which provides a key foothold for the study of HCMV virology, even though HCMV-miRNAs' function remain to be study further in natural diseases such as in autoimmune disease.…”
Section: Discussionmentioning
confidence: 99%
“…Many results suggest that hcmv-miR-US25-1, or hcmv-miR-US25-1-5p, is involved in diverse process; not only cell cycle control, but also virus replication inhibition as well as apoptosis regulation [5,6,32]. It has been reported that hcmv-miR-US25-1-3p has the ability to downregulate CDK6 gene associated with suppress cell cycle progression [19,33]. Here, we identi ed highly HCMV-miRNA expression pattern upon reactivation from latency in vivo, especially for hcmv-miR-US25-1-3p in autoimmune disease patient, which provides a key foothold for the study of HCMV virology, even though HCMV-miRNAs' function remain to be study further in natural diseases such as in autoimmune disease.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we investigated whether FOXO3a could also be a target of HCMV miRNAs. Biochemical and bioinformatic analysis (16) suggested that FOXO3a was a target of HCMV miR-US5-1 and miR-UL112-3p. We cloned the 3' UTR of FOXO3a or 3'…”
Section: Hcmv Mir-us5-1 and Mir-ul112 Cooperatively Target Foxo3amentioning
confidence: 99%
“…Additionally, miR-UL148D protects cells from apoptosis induced by overexpression of IEX-1 (15). Finally, Kim et al reported FAS as a target of miR-UL36-3p, miR-US5-1, and miR-US5-2-3p, Fas associated protein with death domain (FADD) as a target of miR-US5-1, Caspase 3 as a target of miR-US25-2-3p, miR-112-5p, and miR-UL22A-5p, Caspase 2 as a target of miR-US4-5p and Capase 7 as a target of miR-UL22A-3p and miR-US4-3p (16).…”
Section: Introductionmentioning
confidence: 99%
“…The final complex was diluted in Storage buffer with 50% glycerol, snapfrozen in liquid nitrogen and stored at -80 °C. Mutant Cas1-Cas2 complexes were cloned by site-directed mutagenesis as described previously (Kim et al, 2015) and purified as described above. Primers for sub-cloning are listed in Table S1.…”
Section: Protein Preparationmentioning
confidence: 99%